The Development of Curriculum in Indonesia and Its Impact on Primary Education - Zikrullah, Lima; Febrinawati, Riri; Angraini, Lussy Crifela; Putra, Oki Eka (Laboratorium Program Studi Pendidikan Sosiologi Unima, 2023)
This study aims to analyze the development of the basic education curriculum in Indonesia and its impact on the quality of learning through a comprehensive historical and theoretical perspective. The research method uses a qualitative approach with a systematic literature review of academic publications for the period 2010-2023, using thematic analysis to identify key patterns in curriculum evolution and its implementation. The results show that the Indonesian curriculum has undergone a significant transformation from a behaviorist to a constructivist orientation, with three main findings: first, the evolution of curriculum policy reflects adaptation to socio-political dynamics and global demands; second, the implementation of the new curriculum has a positive impact on the quality of learning through increased student engagement, diversification of learning methods, and character development; third, implementation faces complex challenges such as unprepared human resources, limited infrastructure, and lack of stakeholder support. Analysis through the theory of educational change, constructivism, and change management reveals that successful curriculum implementation requires a systemic approach that integrates all components of the education system. This study provides theoretical contributions in understanding the dynamics of curriculum change and practical in developing more effective implementation strategies to improve the quality of basic education in Indonesia.